ANALISIS SIKAP BELAJAR SISWA SELAMA PANDEMI COVID-19 TINGKAT SMA DI KECAMATAN BARUS - Abdul Rahm Habayahan; Mhd. Nau Ritonga; Eva Yanti Siregar (JURNAL MathEdu (Mathematic Education Journal), 2021)
Abstract This study aims to describe the students’ learning attitude during Covid -19 pandemic on Senior High School levelin Barus sub-district. The research was conducted by applying descriptive qualitative. Instrument of the research included questionnaire (Linkert scale) and interview. The respondents of the research consist of 30 students. The result of the research shows 1) based on questionnaire (Linkert scale), students’ learning attitude during Covid -19 pandemic on Senior High School level in Barus sub-district is 61.16% (enough category) and 2) based on interview, students’ learning attitude during the Covid -19 pandemic on Senior High School level in Barus sub-district is not good. It’s concluded online learning during Covid -19 pandemic on Senior High School level in Barus sub-district is inefficient so that solutions must be sought for learning during Covid -19 pandemic on Senior High School level in Barus sub-district.